Contemporary patients with atrial fibrillation are not anticoagulated despite risks of stroke - Insights from GARDENIA - A.K. Kakkar; Marc P. Bonaca; Robert P. Giugliano; Karen Pieper; Dan Bloomfield; Bruce Hug; Janeen Salter; Debra Freedholm; Sanobar Parkar; Saverio Virdone; Herman Sandeep Prakasam; Meg Fluharty; et al. (PLoS ONE, 2026)
Background GARDENIA is a global, multicentre, prospective, non-interventional study in high-risk atrial fibrillation (AF) patients, who were untreated with anticoagulants. Objectives Provide contemporary evidence on reasons for non-treatment with an anticoagulant, and outcomes in high-risk AF patients. Methods GARDENIA enrolled 704 AF patients with a CHA 2 DS 2 -VA score ≥2 and an elevated risk of bleeding (older age (≥70 years), reduced renal function, concomitant antiplatelet or NSAID use, or other conditions associated with increased bleeding risk), and had not been recently treated with an oral anticoagulant (OAC). Patients were followed for at least 4 months. The two-year risks of mortality, stroke and major bleeding with or without direct OACs (DOACs) in these patients was estimated using the GARFIELD risk score. Results History of major bleeding (18.7%), physician-assessed high-risk of bleeding (17.1%), and patient refusal (17.6%) were the top reasons for not initiating OACs. The 100-person-year event rates (95% CI) for mortality, stroke/systemic embolism (SE)/transient ischemic attack (TIA), and ISTH major bleeding were 13.22 (10.33, 16.92), 2.12 (1.14, 3.94), and 2.21 (1.13, 3.91), respectively. GARFIELD risk analysis indicated a 31% and 40% increase in the risk of mortality and stroke, respectively, and a ~ 30% decrease in risk of major bleeding, compared to the estimated risk, had the patients been anticoagulated. The study was prematurely terminated due to low rate of patient accrual. Conclusions Perceived risk of bleeding was the leading cause for non-treatment with OACs in high-risk AF patients. Risk prediction modelling indicated that the benefits of anticoagulation in stroke and mortality reduction outweigh the risk of bleeding.